The Theory of Island Biogeography Revisited - MacArthur, Robert H.; Ricklefs, Robert E.; Losos, Jonathan B. (Book collections on Project MUSE., 2010)
Robert H. MacArthur and Edward O. Wilson's The Theory of Island Biogeography, first published by Princeton in 1967, is one of the most influential books on ecology and evolution to appear in the past half century. By developing a general mathematical theory to explain a crucial ecological problem--the regulation of species diversity in island populations--the book transformed the science of biogeography and ecology as a whole. In The Theory of Island Biogeography Revisited, some of today's most prominent biologists assess the continuing impact of MacArthur and Wilson's book four decades after.